Acinar injury and early cytokine response in human acute biliary pancreatitis. Issue 1 (December 2017) - Jakkampudi, Aparna; Jangala, Ramaiah; Reddy, Ratnakar; Mitnala, Sasikala; Rao, G.; Pradeep, Rebala; Reddy, D.; Talukdar, Rupjyoti
Abstract Clinical acute pancreatitis (AP) is marked by an early phase of systemic inflammatory response syndrome (SIRS) with multiorgan dysfunction (MODS), and a late phase characterized by sepsis with MODS. However, the mechanisms of acinar injury in human AP and the associated systemic inflammation are not clearly understood. This study, for the first time, evaluated the early interactions of bile acid induced human pancreatic acinar injury and the resulting cytokine response. We exposed freshly procured resected human pancreata to taurolithocolic acid (TLCS) and evaluated for acinar injury, cytokine release and interaction with peripheral blood mononuclear cells (PBMCs). We observed autophagy in acinar cells in response to TLCS exposure. There was also time-dependent release of IL-6, IL-8 and TNF-α from the injured acini that resulted in activation of PBMCs. We also observed that cytokines secreted by activated PBMCs resulted in acinar cell apoptosis and further cytokine release from them. Our data suggests that the earliest immune response in human AP originates within the acinar cell itself, which subsequently activates circulating PBMCs leading to SIRS. These findings need further detailed evaluation so that specific therapeutic targets to curb SIRS and resulting early adverse outcomes could be identified and tested.